Studi Eksperimental Karakteristik Capillary Rise Material Karbon Aktif Bamboo Betung (Dendrocalamus Asper) Sebagai Material Pad Sistem Direct Evaporative Cooling - Lumban Gaol, Rony Standi; Wijaksana, Hendra; Astawa, Ketut (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstract The increase in global temperature, including Indonesia, which occurred at the end of the 21st century, resulted in an increase in the need for electrical energy for the use of Air Conditioner compressor-based (AC) systems. In addition to the high demand for electrical energy, the use of refrigerant in the air conditioning system can endanger environmental sustainability, where large amounts of refrigerant released into the surrounding air can cause unfavorable environmental pollution in the form of global warming. Therefore, a cooling system that is more energy efficient and environmentally friendly is needed. Evaporative Air Cooler using a direct evaporative cooling system can be an option, where the cooling effect obtained is the result of evaporation that occurs in the pad material that has been wetted by water. The basic material for the pad material used is local bamboo betung from Bali. This study aims to determine the value of capillary rise in each different test specimen. By using a carbonization temperature of 500°C, then activated with a temperature of 600°C and holding time variations, namely 0 (without holding time), 30 minutes, 60 minutes. The results of all these tests indicate that the carbonization specimen at 500°C with an activation of 600°C with a variation of 30 minutes holding time or ACRB 500 HT 30 has the highest capillary rise value of 42.79 x 10-2 m and makes this specimen more potential to be used as raw material. pad material in direct evaporative cooling system. Keywords: Direct evaporative cooling, bamboo betung, carbonization, activation, capillary rise.